Effect of reconstitution technique on the nutritive value of pearmillet grain and performance of growing lambs - Singh, Jai Dev; Lohan, O P (The Indian Journal of Animal Sciences, 2012)
In vivo experiments (2) were conducted to determine the nutritive value of reconstituted pearlmillet grams and effect of their feeding on the performance of lambs. The first experiment was conducted on 15 lambs to find out the nutritive value of raw pearlmillet grains (T1), reconstituted pearlmillet grains and 1 % urea-treated pearlmillet grains. DCP increased due to reconstitution, and it was further increased to 7.76 ± 0.08% due to addition of 1 % urea. The TDN values were 66.45 ± 3.59, 75.73 ± 2.31 and 79.58 ± 1.55%, for T1, T2 and T3 treatments as compared to T1 treatment.The second experiment was conducted on 20 growing lambs divided into 4 groups, having 5 lambs in each group. The barley of control ration (T1) was replaced with raw pearlmillet grains (T2 ) with reconstitution (T3) and reconstituted urea-treated pearlmillet grains (T4 ) respectively. All the rations were isonitrogenous. The average growth rate was higher in groups T3 and T4;and was lowest in T2 group, however, the differences were nonsignificant. The feed (DM) consumed per kg gain was 7.43 ± 0.43, 9.24 ± 0.95, 7.45± 0.32 and 7.33 ± 0.80 kg for groups T1, T2 and T3 and T4, respectively. The results indicated that reconstitution of pearlmillet grains increased the platability, feed utilization and performance of growing lambs.